Modelling total quality management in the Malaysian composite manufacturing industry - Akmal, Suriati; Hasim, Nur Aiman Hanis; Sayed Nordin, Sayed Kushairi; Mamat, Mohd Fauzi; Hambali, Ruzy Haryati; Alshamsi, Abdulla Thamer Jumma Aldharif; Pawenang, Supawi (Penerbit Akademia Baru, 2022)
This paper investigates the enabler factors of total quality management (TQM) practices for a composite manufacturing company in Melaka, Malaysia. Leadership (L), training and education (TE), supplier management (SM), customer focus (CF), bench marking (B), continuous improvement (CI), employee relations (ER), and strategic planning (SP) were considered in this paper. They are the critical TQM elements that influence TQM processes (Y). A questionnaire was used to collect data from 27 employees of a composite manufacturing company in Melaka, Malaysia and analyzed using multiple regression analysis. Five out of the eight hypotheses positively fit with the conceptual model and show a positive effect of TQM practices. The research findings indicate that enabler factors, namely leadership (L), continuous improvement (CI), supplier management (SM), bench marking (B) and strategic planning (SP), have positive and significant effects on successful TQM practices. This study would benefit managers significantly to increase strategic planning, supply chain management, and bench marking through TQM practices.